Words and Things: The Uncertain Place of Philology in Intellectual History. (4th May 2018) - Cryle, Peter
ABSTRACT: This paper considers the ease and the difficulty of adapting the habits of philology to the exigencies of intellectual history. The title chosen by Michel Foucault for one of his major historical studies referred to 'words and things', but the relation between those two is not given once and for all. Foucault developed the notion of discourse, which involved articulated sets of words. Discourses he understood to be sayable propositions corresponding to thinkable things. Since the 1970s and 1980s, Foucault's influence on the humanities and social sciences has been great, and there now exists at least one field of research that owes direct allegiance to his view of discourse: the field of intellectual history. Scholars have come to intellectual history after being trained in a range of disciplines: not just history of various kinds, but philosophy, studies in religion and literary studies. This paper will ask specifically what it can mean in practice to bring to the historical study of discourses a training in which philology has played a part. In the absence of a putative love of discourse, what might it mean to take words as objects of close historical attention?